IN VIVO STUDY OF THE EFFECT OF A STRONTIUM-‐RICH INJECTABLE SYSTEM ON BONE REGENERATION, USING A SHEEP MODEL - Machado, C. (2016)
Bone has the capacity to regenerate as part of the repair process,being newly formed boné indistinguishable from the adjacente uninjured bone. However,there are cases in which boné regeneration is required in large quantity, beyond the normal potential for self-‐healing, such as for lesions caused by trauma, infection, tumour resection or cases in which the regenerative process is compromised such as avascular necrosis and osteoporosis. Biomaterials such as alginate are very promising due to its ability to form hydrogels in situ under mild conditions in the presence of divalente cations. The combination with ceramic microspheres results in a mechanically improved injectable system, adequate for minimally invasive procedures. Moreover, the combination with chemical elements such as strontium, described as promoter of boné formation, inhibiting boné resorption provides ion Exchange between the implanted biomaterial and surrounding tissue, enhancing boné regeneration. Our goal is to study in na invivo sheep model, the effect of na injectable system composed of strontium doped hydroxyapatite microspheres, delivered in na alginate vehicle, crosslinked with strontium.